Strategi Peningkatan Mutu SDM Pendidikan Berdasarkan Sistem Broad Based Education - Taufiqurrahman Taufiqurrahman (Islamic University of Indonesia, 2008)
Although the educational programe had been on going process since56 years ago in Indonesia, but this state didn’t has provided qualifiedhuman resources. Since 32 years ago of The New Order Government,educational sector development has never been placed as a primepriority of development. Its effect is Indonesian educational quality beingworse than the other countries in southest Asia likes Malaysia, Pilipina,Singapura, and Thailand. Indonesia is being effected by dimentional multicrises since tvelve years ago and untill now, it is still degraded by itspast time which avoided educational development. Moreover, the aotherstates which effected by the same problem like Indonesia could reformby paying attention greater toward educational development sector. Theycould reform faster and being better states bacause they have humangood resource quality. By broad based education system and high basededucation system, we hope the quality of Indonesian human resources willbe more better in the next.